STRATEGI GURU DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI MEDIA DIGITAL DI TK YAA BUNAYYA - Mutmainnah, Atri; Anhar, Ade S; Mulyadi, Wahyu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the strategies implemented by teachers in improving the quality of learning through the use of digital media at Yaa Bunayya Kindergarten. In today's digital era, the use of technology in early childhood education is an important step in creating an interesting and effective learning process. The method used in this study is descriptive qualitative with data collection techniques including observation, interviews, and documentation. The results of the study revealed that teachers at Yaa Bunayya Kindergarten implemented various strategies, such as the use of educational videos, interactive learning applications, and the use of digital platforms to communicate with parents. These strategies have been proven to be able to increase children's participation in learning activities and strengthen collaboration between teachers and parents. Thus, it can be concluded that the integration of digital media in the learning process has a positive impact on the quality of education at Yaa Bunayya Kindergarten.